2010
DOI: 10.1073/pnas.1009566107
|View full text |Cite
|
Sign up to set email alerts
|

Most harmful algal bloom species are vitamin B1and B12auxotrophs

Abstract: Eutrophication can play a central role in promoting harmful algal blooms (HABs), and therefore many HAB studies to date have focused on macronutrients (N, P, Si). Although a majority of algal species require exogenous B vitamins (i.e., auxotrophic for B vitamins), the possible importance of organic micronutrients such as B vitamins (B 1 , B 7 , B 12 ) in regulating HABs has rarely been considered. Prior investigations of vitamins and algae have examined a relatively small number of dinoflagellates (n = 26) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
290
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 248 publications
(308 citation statements)
references
References 53 publications
16
290
1
1
Order By: Relevance
“…The light stability of vitamin-B 1 is consistent with the use of an artificial white light source in our experiments, as vitamin-B 1 light degradation has been observed only under x-rays, gamma rays and UV irradiation (Gubler, 1984). Vitamin-B 1 concentrations in the growth medium were within the threshold levels considered limiting for some phytoplankton species (Carlucci and Silbernagel, 1966;Tang et al, 2010;Paerl et al, 2015), suggesting that bacteria could have been vitamin-B 1 -deficient during our experiments.…”
Section: Proton Motive Force (Pmf)-dependent Processesmentioning
confidence: 89%
“…The light stability of vitamin-B 1 is consistent with the use of an artificial white light source in our experiments, as vitamin-B 1 light degradation has been observed only under x-rays, gamma rays and UV irradiation (Gubler, 1984). Vitamin-B 1 concentrations in the growth medium were within the threshold levels considered limiting for some phytoplankton species (Carlucci and Silbernagel, 1966;Tang et al, 2010;Paerl et al, 2015), suggesting that bacteria could have been vitamin-B 1 -deficient during our experiments.…”
Section: Proton Motive Force (Pmf)-dependent Processesmentioning
confidence: 89%
“…A. anophagefferens, strain CCMP1984, was isolated in 1986 from Great South Bay, New York, on Long Island's south shore, and was made axenic and publicly available in 2003. Its vitamin auxotrophy has been previously confirmed in culture and via genomic sequencing (Tang et al 2010;. Cultures obtained from Provasoli-Guillard National Center for Marine Algae and Microbiota were grown in GSe medium (Tang et al 2010) made with artificial salts with and without the addition of B vitamins.…”
Section: Methodsmentioning
confidence: 99%
“…B vitamins have been found to limit the accumulation of phytoplankton biomass in estuaries where blooms of A. anophagefferens frequently occur (e.g., Quantuck Bay, New York; Sañ udo-Wilhelmy et al 2006). Furthermore, recent laboratory experiments (Tang et al 2010) demonstrated that A. anophagefferens is auxotrophic with respect to both vitamins B 1 and B 12 , a finding confirmed by the presence of genes for B 12 -dependent methionine synthase (metH), but not the B 12 -independent homolog (metE) in its recently sequenced genome Helliwell et al 2011). No field study, however, has investigated the role of B vitamins in HAB events, including brown tides caused by A. anophagefferens, in .…”
mentioning
confidence: 99%
“…This inference was based on the fact that many species of eukaryotic phytoplankton require vitamins when they are cultured in the laboratory (3)(4)(5)(6)(7). Although it was thought that marine prokaryotes were the major producers of vitamins in the sea (4), genomic data indicate that it is common for both eukaryotic phytoplankton and bacterioplankton to be auxotrophic for at least one B vitamin, mainly because they lack the complete biosynthetic pathways required to produce them (8).…”
mentioning
confidence: 99%